ECONOMIC SECURITY MAINTAINING AS ECONOMIC GROWTH LIMITATION - I. Kirshin (Russian Journal of Economics and Law)
Basing on elaboration and analysis of economic-mathematical model, the article grounds the economic growth limitations in the context of economic security maintaining. The author proposes a hypothesis that the absolutization of the technogenic aspect of the present economic growth can lead to the qualitative transition to non-economic growth. The criterion of economic security ensuring is defined as the equity of economic growth marginal utility and the marginal costs reflecting the value of economic loss imposed by it.